Glucocorticoid receptor signaling is required for acclimation of skeletal muscle to hypobaric hypoxia - Whitcomb, Luke, author; Chicco, Adam, advisor; Maresh, Ryan, advisor; Melby, Christopher, committee member (Colorado State University. Libraries, 2022)
Hypobaric hypoxia (HH) encountered at high altitudes acutely impairs aerobic exercise capacity, which partially recovers following 1-2 weeks of acclimation to chronic HH. Persistent elevations in serum glucocorticoids occur during HH exposure, but their role in these acute and chronic physiological responses is unclear. We tested the hypothesis that glucocorticoid signaling is essential for the acclimation of aerobic exercise capacity to chronic HH, in part by mediating adaptive changes in skeletal muscle metabolism. Male F344 rats were administered the glucocorticoid receptor antagonist RU486 (RU; 60 mg/kg/d in chow) or no drug for 5 days prior to 15 days of continued normoxia (Fort Collins, CO; elevation 5,003 feet) or HH (simulated 17,200 feet in a hypobaric chamber) with or without continuous RU treatment (N=4-8/group). Graded treadmill exercise tests (GXT) were conducted on a motorized treadmill in normoxia, during acute HH exposure, and in HH after 15 days of HH acclimation. As expected, acute HH reduced GXT performance compared to normoxia in all rats, which improved following 15 days of acclimation to HH. RU pretreatment did not impact hypoxic GXT performance, but continuous treatment abolished improvements in GXT performance following chronic HH. RU attenuated HH-induced increases in hematocrit and muscle fatty acid oxidation efficiency assessed by high-resolution respirometry ex vivo, suggesting that glucocorticoid signaling may improve muscle oxygen utilization in response to chronic HH. RU also prevented HH-induced decreases in pyruvate dehydrogenase expression and increases in Krüppel-like factor 15, proteolysis and branched-chain amino acid aminotransferase in glycolytic muscle, implicating glucocorticoid signaling in a rewiring of glucose and protein catabolism to rid the cell of excess nitrogen in HH. In conclusion, these results demonstrate that glucocorticoid receptor signaling is essential for the acclimation of aerobic exercise capacity to HH, perhaps by mediating improvements in the bioenergetic efficiency of skeletal muscle metabolism.
Keywords: high altitude; mitochondria; skeletal muscle; hypobaric hypoxia; fiber type; proteolysis